Access to assistive technology among students with visual impairment in higher education institutions in Tanzania: challenges and coping mechanisms - Kisanga, Dalton H; Kisanga, Sarah E (University of Dar es Salaam Library Journal, 2021)
Access to assistive technology (AT) among students with visual impairment is highly dependent on their availability and the technical know-how of the users. This study reports the challenges students with visual impairment experience in accessing assistive technology and their coping mechanisms in Tanzania ' s higher education institutions. The study used semi-structured interview and an open-ended questionnaire to collect data from17 students with visual impairment and four transcribers. The resultant qualitative data was subjected to descriptive and thematic analyses. The study has identified lack of knowledge on how to apply assistive technologies, limited ICT infrastructures, and shortage of assistive technology tools as major challenges for students with visual impairment when accessing AT in higher education institutions. Two major categories of problem-focused coping €”social support networks and personal efforts €”emerged. The former covers support from skilled/sighted peers and institutions in terms of training on assistive technology. The later deals with private learning through the Internet and other sources, sharing of available resources, use of smart phones, utilisation of alternative devices and borrowing of AT devices from other colleagues. Thus, the study recommends higher education institutions to provide sufficient and sustainable financial investment in AT in addition to improving their affordability to ensure that students with VI attain education equity. Similarly, students with visual impairment and their transcribers need regular training on assistive technology to enhancet heir accessing of assistive technologies.